STATUS YODIUM TUBUH ANAK SEKOLAH DASAR DAN IBU HAMIL DI 25 DATI II DI PROVINSI JAWA BARAT - Iman Sumarno (Persagi, 1998)
Iodine deficiency has been known to have adverse impact on human resources. Iodine deficiency disorders (IDD) range from reproductive failure to the impairment of intellectual and productivity. A survey in 1982 found that iodine deficiency was spread all over the islands in lndonesia. Therefore, the government of Indonesia has been intensifying the programs to control IDD. However, the national data of IDD are available only from the IDD survey in 1982. In order to design a sound planning the government needs up dated data. Since 1995 the government of Indont!sia has been conducting the IDD mapping in all provinces in Indonesia. One of them is the IDD survey in the province of West Java. This article aims to present the status of iodine sufficiency in the body of school-children and pregnant women from the IDD survey in West Java. The study was designed to provide information that represents iodine status at kabupaten (district) level. It was curried out in all kecamatan (sub-district) in the province of West Java. In each kecamatan 20% of the villages are randomly selected. It covered 40 to 102 villages in each district. Within each sub-district 300 schoolchildren aged 6-12 years were examined. These children were distributed equally in each the selected villages within the sub-district. One elementary school was randomly selected from each selected village. At least 300 schoolchildren divided by the amount of selected villages within the kecamatan were proportionally selected from each grade. Tlte number of sample pregnant women needed from each district is 300. The number of sample pregnant women in each kecamatan is 300 divided by the number of sub-district within the district. These samples are distributed equally in the villllges within each sub-district. The data were goitre rate, iodine excreted in the urine (UIE) and the level of blood TSH of pregnant women. The classification of iodine deficiency endemic area from WHO was employed in the analysis. It was found that based on the TGR in schoolchildren the province of West Java was classified as a non-endemic goitre area. However, based on the UIE it was classified as a mild iodine deficiency area. At the district level the TGR in school children was positively highly correlated with the TGR in pregnant women (0,8). The median of UTE was negatively highly correlated with the TGR in pregnant women and the TGR in schoolchildren. The median TSH was negatively correlated with median UIE but not with TGR either of schoolchildren or of pregnant women.